Discourse Quality in Times of Populism: An Analysis of German Parliamentary Debates on Immigration Policy (Communication & Society, 2018)
Right-wing populists are on the rise in Europe in the last decade. Their populism undermines one of the central pillars of democracy, the political discourse. Populism affects the quality of political debates in parliaments. With the emergence of the “Alternative für Deutschland” (AfD) a populist party became relevant nationally for the first time in over sixty years. By applying the concept of Cognitive Complexity as an instrument to measure deliberative quality, we analyze to what extend the discourse quality in the German Bundestag in debates on immigration policies varied over the 18th legislative period. Cognitive Complexity is measured quantitatively by applying a linguistic approach based on the LIWC dictionary. Despite our initial expectations, there are no trends detectable and the rise of the populist AfD does not alter the discourse quality so far. Nonetheless, there exist major differences in discourse quality between the parties, most notably opposition parties have a lower discourse quality in their statements than governing parties. In addition, individual characteristics of the speaker such as gender, age or electoral type do not render any differences. However, there seem to be differences depending on the federal state in which the speaker’s electoral district lies.